Asuhan Kebidanan Komunitas pada Keluarga Tn. “A” dengan Anemia Ringan pada Ibu Hamil di Dusun Ngolang Desa Kuta Kecamatan Pujut - Baiq Khairiyatunnisa; Hasrun Ningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study uses the USG method (Urgency, Seriousness, and Growth). The sample or target is pregnant women in the third trimester with Mild Anemia, counseling was carried out at the Kuta Health Center, Kuta Village which was held on Sunday, November 2, 2024. So the author will relate the concept or theory to the case of Mrs. R starting from the assessment, data interpretation, potential diagnosis, problem anticipation, planning, implementation and evaluation. The author discusses the gaps and similarities between the theory and the existing case. Research results Based on midwifery care that has been carried out on pregnant women in Mrs. R GII PI AO with mild anemia in Ngolang Hamlet, Kuta Village using the 7 Varney steps, the results obtained that subjective data, especially on the main complaint, namely the mother said she was weak, dizzy, tired quickly, short of breath and pain in the waist and legs. And objective data, namely the mother's general condition is good, anemic conjunctiva and Hb levels of 9.2 g%. So that an obstetric diagnosis was obtained in Mrs. R with mild anemia during pregnancy. Therefore, immediate action and collaboration are needed for Mrs. R with mild anemia in Dusun Ngolang, Kuta Village, with the result that in this case, no collaborative action was taken because there were no indications and data to support the action. The results of the actions that have been carried out on Mrs. R with mild anemia in Dusun Ngolang, Kuta Village, with the result that the care that has been given was successful, marked by changes in the mother's Hb levels from 9.2 g% to 10.8 g%. Keywords: , ,